English as a lingua franca and Critical Language Pedagogy: paths to the decolonization of ELT - Pimentel Siqueira, Domingos Sávio (Árboles y Rizomas, 2025)
English is the global language of contemporary times. Its worldwide expansion, interpreted in different ways, can be attributed to various factors, with colonialism perhaps being the most historically significant. Tied to this, the English Language Teaching (ELT) industry emerges as a multibillion-dollar sector whose origins also trace back to colonialism. Among the interpretations of this expansionist phenomenon, English as a Lingua Franca (ELF) stands out as a transcultural zone of power that, due to its unique characteristics, can foster dialogues capable of challenging traditional ELT models by exposing their (neo)colonial roots. In this article, I propose a dialogue between ELF and Critical Language Pedagogy (CLP), an approach that views additional language teaching as a tool for social justice. I argue that both teachers’ daily practices and teacher education play a crucial role in questioning the historical foundations of ELT in the Global North, promoting epistemic plurality and other transformative possibilities in English classrooms. Finally, the reflections presented here are grounded in the movement “ELF feito no Brasil,” conceived by Brazilian scholars who seek to integrate a political and decolonial approach to ELF research, aiming to legitimize knowledge production based on the experiences of the Global South.
Keywords: English as a lingua franca; Critical language pedagogy; English language teaching; (de)coloniality